Procedural validity of the AUDADIS-5 depression, anxiety and post-traumatic stress disorder modules: Substance abusers and others in the general population. (1st July 2015) - Hasin, Deborah S.; Shmulewitz, Dvora; Stohl, Malka; Greenstein, Eliana; Aivadyan, Christina; Morita, Kara; Saha, Tulshi; Aharonovich, Efrat; Jung, Jeesun; Zhang, Haitao; Nunes, Edward V.; Grant, Bridget F.
Highlights: Procedural validity of DSM-5 AUDADIS-5 mood and anxiety diagnoses was examined. Sample: current regular substance abusers and others in the general population. Validation procedure: blinded clinician-administered PRISM-5 interviews. AUDADIS-5 validity: fair-substantial in substance abusers and others. AUDADIS-5 measures are useful in regular substance abusers and others. Abstract: Background: Little is known about the procedural validity of lay-administered, fully-structured assessments of depressive, anxiety and post-traumatic stress (PTSD) disorders in the general population as determined by comparison with clinical re-appraisal, and whether this differs between current regular substance abusers and others. We evaluated the procedural validity of the Alcohol Use Disorder and Associated Disabilities Interview Schedule, DSM-5 Version (AUDADIS-5) assessment of these disorders through clinician re-interviews. Methods: Test−retest design among respondents from the National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III): (264 current regular substance abusers, 447 others). Clinicians blinded to AUDADIS-5 results administered the semi-structured Psychiatric Research Interview for Substance and Mental Disorders, DSM-5 version (PRISM-5). AUDADIS-5/PRISM-5 concordance was indicated by kappa ( κ ) for diagnoses and intraclass correlation coefficients (ICC) for dimensional measures (DSM-5 symptom or criterion counts). Results were compared between current regular substance abusers and others. Results: AUDADIS-5 and PRISM-5 concordance for DSM-5 depressive disorders, anxiety disorders and PTSD was generally fair to moderate ( κ  = 0.24−0.59), with concordance on dimensional scales much better (ICC = 0.53−0.81). Concordance differed little between regular substance abusers and others. Conclusions: AUDADIS-5/PRISM-5 concordance indicated procedural validity for the AUDADIS-5 among substance abusers and others, suggesting that AUDADIS-5 diagnoses of DSM-5 depressive, anxiety and PTSD diagnoses are informative measures in both groups in epidemiological studies. The stronger concordance on dimensional measures supports the current movement toward dimensional psychopathology measures, suggesting that such measures provide important information for research in the NESARC-III and other datasets, and possibly for clinical purposes as well.